The project “D.E.A.Th. by Eros to Thanatos AIDS and Sexually Transmitted Diseases”. A multimedia exhibition as a means of prevention of sexually transmitted infections (Italian Journal of Public Health, 2010)
Background: An educational intervention on Sexually Transmitted Diseases (STDs) accompanied by amultimedia exhibition was proposed in order to verify the effectiveness of an exhibition as a tool forprevention, to increase awareness in youth and to evaluate whether it yielded changes in the sexualbehaviour of its’ visitors. The Target population were high schools and university students.Methods: The Exhibition consisted of a historical overview and four other sections: biological and clinicalaspects, epidemiology, prevention and a section called the Red Zone with clear and explicit images relating toSTDs. The exhibition was supported by three observational studies carried out on about2000 students of twoHigh Schools and the university in the city of Cassino, Italy. Data collection took place through three differenttypes of “ad hoc” questionnaires. The Statistical analysis carried out was that typical of cross-sectionalsurveys. We utilized the statistical program Epi-Info 3.5.Results: Regarding survey 1, 48% of 529 students taking part said that the exhibition had contributed“enough” for them to acquire new knowledge, 75.2% had already had sexual intercourse and 37.7% ofthem did not change their sexual habits. Relative to survey 2, 583 responded to the pre test and 403 post-tests returned. Regarding knowledge, data obtained from processing of pre-tests showed how 63.9% of thesample did not know how many STDs existed, whilst this value dropped in post test answers to 49.2% .AIDS was the best known disease (96%) whilst other STDs were little known. The educational interventionpartly increased these percentages. With regard to sexual practices although 43% of the sample claimedto have already had sexual intercourse (66% male and 34% female). The family doctor is seen by a highpercentage of young people (70% - 68.6%) as the first figure which should address an individual affected by asexually contracted disease. Only 46% (pre and post tests) recognized at risk groups such as “drug addicts”,homosexuals and heterosexuals.Eight hundred university students participated in Survey 3. The sample had good knowledge about HIVtransmission and the AIDS disease and 93% of respondents knew how to avoid infection. They identifieddrug users and homosexuals as the most prone to infection to HIV, while awareness of infection risk amongheterosexuals was less marked. Despite its importance, awareness of condom use was worrying as only44.2% reported to always one.Conclusions: The exhibition can be considered as an effective prevention tool for new knowledge acquisitionbut not for the modification of behaviours already present. Even in this study, it looks like the long-termeffects, in populations who have had health education interventions with the models of behavioural change,are not sufficiently protective . Therefore, it is necessary to intensify efforts to broadly apply the mosteffective models of self empowerment in order to change risk behaviours.
Keywords: sexually transmitted infections; youth; prevention